Afghan and Kurdish refugees, 8-20 years after resettlement, still experience psychological distress and challenges to well being - Cheryl M. R. Sulaiman‐Hill; Sandra C. Thompson (Elsevier, 2012)
Abstract Objective: To examine the resettlement experiences and provide data of well being and psychological distress for Afghan and Kurdish refugees settled between eight and 20 years in New Zealand and Australia. Methods: Participants completed the Kessler‐10 Psychological Distress Scale (K10) and Personal Well Being Index (PWI) for subjective well being. A mixed methods approach was used, with participants also discussing during interview resettlement difficulties, quality of life (QOL) and sources of stress. Results: Data from 81 Muslim participants is reported; all spoke English, were generally well educated with 88% having secondary or tertiary level education, and the majority of those resettled before 2001 lived in Perth. Although psychological distress levels were mostly within the low‐moderate risk range, significant differences were observed by gender and employment status. Participants identified a range of ongoing stressors with unemployment of particular concern. Social isolation and a sense that they would never really 'fit in' was also reported by some. Participants particularly valued the safety and improved quality of life in their host communities. Conclusions: Despite their appreciation of the overall resettlement experience, too much time to introspect, separation from family, status dissonance and still occasionally feeling overwhelmed by resettlement challenges is a long‐term ongoing reality for some former refugees. Implications: Former refugees continue to struggle with unemployment, possible discrimination and loss of status long‐term.